A System Dynamics Model for Industrial Investment in the Housing Sector Considering Monetary and Non-Monetary Economic Variables - Neda Farkoush; Arash Hadizadeh; Sadegh Abedi (اقتصاد شهری, 2025)
his study aims to present a comprehensive model for analyzing industrial investment in the housing sector from 2005-2023. The proposed model, developed using system dynamics methodology, incorporates a range of economic factors, including monetary variables (such as inflation, interest rates, and exchange rate fluctuations) and non-monetary variables (such as population growth, urbanization, and migration), along with fiscal, regulatory, and technological policies. The model employs reinforcing and balancing loops to examine the complex interactions among these variables. The results indicate that exchange rate fluctuations and inflation are major deterrents to investment. At the same time, government financial support and the adoption of advanced technologies can enhance productivity and help balance supply and demand. Furthermore, technological advancements play a critical role in reducing construction costs and accelerating project completion. The innovation of this study lies in the development of a dynamic model capable of simulating the long-term behavior of key variables and providing actionable solutions to reduce market volatility and improve sustainability in the housing sector. The findings offer valuable insights for policymakers and planners in making informed decisions to manage investment in the housing industry effectively.